Towards Neuroinclusive Public Parks: A Theory-Informed Wayfinding Framework for Landscape Design Practice - Pattamon Selanon; Akarawit Sapsangthong (Architecture, 2026)
Public parks support health, wellbeing, and social inclusion, yet conventional wayfinding approaches remain largely focused on physical mobility and directional navigation, often overlooking the cognitive and sensory experiences of neurodivergent users. This study develops a theory-informed framework for neuroinclusive wayfinding design through an integrative literature review. Using a Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA)-informed protocol, 106 core sources were synthesized from landscape architecture, environmental psychology, public health, and neurodiversity research. A qualitative theory-building approach combining thematic analysis, theoretical mapping, and abductive synthesis identified four themes: Cognitive Navigation and Environmental Legibility, Sensory Processing and Environmental Regulation, Restorative Landscapes and Nature-Based Wellbeing, and Inclusive, Adaptive, and Neurodiverse Design. These themes were subsequently translated into eight environmental challenges and operationalized into eight neuroinclusive wayfinding design criteria organized within four support domains. The resulting framework conceptualizes wayfinding as a cognitive–sensory support system rather than a purely navigational function, linking interdisciplinary evidence to practical landscape architectural design strategies. By integrating fragmented knowledge across multiple disciplines, the study provides a foundation for future validation and the advancement of neuroinclusive public park design.